Acoustic respiration rate and pulse oximetry-derived respiration rate: a clinical comparison study. - Eisenberg, Michal E.; Givony, Dalia; Levin, Raz (Journal of Clinical Monitoring & Computing, 2020)
Respiration rate (RR) is a critical vital sign that provides early detection of respiratory compromise. The acoustic technique of measuring continuous respiration rate (RRa) interprets the large airway sound envelope to calculate respiratory rate while pulse oximetry-derived respiratory rate (RRoxi) interprets modulations of the photoplethsymograph in response to hemodynamic changes during the respiratory cycle. The aim of this study was to compare the performance of these technologies to each other and to a capnography-based reference device. Subjects were asked to decrease their RR from 14 to 4 breaths per minute (BPM) and then increase RR from 14 to 24 BPM. The effects of physiological noise, ambient noise, and head movement and shallow breathing on device performance were also evaluated. The test devices were: (1) RRa, Radical-7 (Masimo Corporation), (2) RRoxi, Nellcor™ Bedside Respiratory Patient Monitoring System (Medtronic), and (3) reference device, Capnostream20p™ (Medtronic). All devices were configured with their default settings. Twenty-nine healthy adult subjects were included in the study. During abrupt changes in breathing, overall RRoxi was accurate for longer periods of time than RRa; specifically, RRoxi was more accurate during low and normal RR, but not during high RR. RRoxi also displayed a value for significantly longer time periods than RRa when the subjects produced physiological sounds and moved their heads, but not during shallow breathing or ambient noise. RRoxi may be more accurate than RRa during development of bradypnea. Also, RRoxi may display a more reliable RR value during routine patient activities.